LAND DISPUTE BETWEEN MAMAK AND NEPHEW OVER CENTURIES-OLD INHABITED LAND BASED ON JUDGE'S DECISION - Yulidia, Yulidia; Sudiro, Amad (Awang Long Law Review, 2025)
Minangkabau society adheres to a matrilineal kinship system, where ancestral land (pusaka tinggi) is inherited collectively by female family members and cannot be transferred outside the lineage. The legal relationship between customary law communities and their land creates inherent rights that ensure communal ownership and usage. However, disputes often arise regarding land ownership and inheritance due to differing interpretations of customary laws. This research aims to analyze the resolution of inherited land disputes within the Minangkabau community, specifically in the Batang Kapas area, based on the court decision in case number 31/Pdt.G/2013/PN.Pin. The study employs normative legal research methods, focusing on statutory, case law, historical, and conceptual approaches. Data is gathered through document analysis of court decisions, legal literature, and Minangkabau customary law principles. The findings indicate that the resolution of customary land disputes heavily relies on historical evidence, family genealogy, and the existence of ancestral graves on the disputed land. The court ruled in favor of the defendants, considering that the land had been occupied for generations by the same lineage, as evidenced by the presence of family burial sites and testimonies from customary leaders. The decision highlights the strong influence of Minangkabau customary law in determining rightful ownership, emphasizing the principle of collective inheritance and the role of traditional leaders in dispute resolution. This study underscores the enduring relevance of customary law in modern legal frameworks and its significance in preserving communal property rights within indigenous communities.